The Association of Physical Activity With Overweight/Obesity and Type 2 Diabetes in Nepalese Adults: Evidence From a Nationwide Non‐Communicable Disease Risk Factor Survey - Ritesh Chimoriya; Kritika Rana; Jonas Adhikari; Sarah J. Aitken; Prakash Poudel; Aayush Baral; Lal Rawal; Milan K. Piya (Obesity Science & Practice)
ABSTRACT Background The rising prevalence of obesity and type 2 diabetes (T2DM) is a significant public health concern, particularly in low‐ and middle‐income countries. This study aimed to explore the association between physical activity levels, overweight/obesity, and T2DM in a nationwide survey of Nepalese adults. Methods This was a secondary analysis of the 2019 non‐communicable diseases (NCD) risk factors STEPS survey conducted in Nepal. Demographic and anthropometric data, body mass index (BMI) and T2DM status were collected along with assessment of physical activity using Global Physical Activity Questionnaire (GPAQ). A two‐stage data analysis was conducted, first using descriptive statistics to summarize participant characteristics and differences across BMI and T2DM status, and then applying multivariate analyses to assess associations between physical activity levels, BMI and T2DM. Results Of the 5284 participants included, 28.0% had overweight/obesity, 5.8% had obesity, and 6.5% had T2DM. The mean age of the participants was 40.1 years (95% CI: 39.8–40.6), and 63.9% were female. The overall physical activity energy expenditure was higher in the lean group (BMI < 25 kg/m2) compared to the those with overweight/obesity, and among participants without T2DM compared to those with T2DM. Sedentary behavior was more common among individuals with overweight/obesity and T2DM. A higher proportion of participants with low physical activity was observed in the overweight/obesity group compared to the lean group (8.9% vs. 6.3%) and the T2DM group compared to the non‐T2DM group (11.7% vs. 6.7%). Low physical activity was associated with overweight/obesity (OR:1.4; 95% CI:1.1–1.8), obesity (OR:2.1; 95% CI:1.5–2.3), T2DM (OR:1.6; 95% CI:1.1–2.3) and T2DM in the presence of obesity (OR:3.6; 95% CI:1.7–7.8). Conclusion This study highlights the low rates of physical activity and higher rates of sedentary behavior among adults with overweight/obesity and T2DM in Nepal. Public health interventions promoting physical activity and reducing sedentary behavior may help reduce the burden of these NCDs.